CONTROVERSIAL ISSUES OF THE SYSTEM OF PUNISHMENTS IN THE SCIENCE OF CRIMINAL LAW OF UKRAINE - Оробець, Костянтин (SWorldJournal, 2024)
The article is devoted to the consideration of complex problems of the system of punishments under the criminal law of Ukraine. The problems of defining the meaning of the concept of "system of penalties", the place of certain types of punishments in the